Chlamydia screening, retesting and repeat diagnoses in Cornwall, UK 2003–2009. Issue 1 (28th September 2012) - Turner, Katy M E; Horner, Paddy J; Trela-Larsen, Lea; Sharp, Matt; May, Margaret
Abstract : Objectives: This study aims to describe the patterns of testing and retesting for chlamydia in Cornwall during the first 5 years of the National Chlamydia Screening Programme. We evaluate the factors associated with retesting and estimate the incidence of chlamydia diagnosis and repeat diagnosis. Methods: Study design: Secondary database analysis. Selection criteria: men and women tested for chlamydia between March 2003 and January 2009 in Cornwall, aged ≥12 years and ≤25 years at the first test. The factors associated with retesting in those with at least one known test result and at least 14 days follow-up time were analysed using Cox regression and the incidence of diagnosis and repeat diagnosis were calculated. Results: The final dataset consisted of 71 066 records from 49 941 individuals; of whom 59.0% were female and 75.4% were only tested once. There were 48 375 individuals with at least one known test result (negative or positive) and at least 14 days follow-up, included in the Cox regression analysis. Factors associated with testing more than once were (adjusted HR, 95% CI): being female (2.24; 2.14 to 2.34) and initially testing positive (1.43; 1.35 to 1.51). The positivity at first episode declined from 13.2% (1077 cases) in 2003/2004 to 5.8% (843 cases) in 2008/2009. The incidence of diagnosis at the second test was 5.9 per 100 person years in those testing negative at the first test compared with 18.1 per 100 person years in those initially positive. Discussion: Most individuals in this analysis were tested only once, but the testing volume and proportion of repeat tests were highest at the end of the study period. As the testing rate stabilises to 30% coverage, maintaining retesting rates in those previously tested and especially in those previously diagnosed with chlamydia will be necessary for the sustainability of the screening programme. Conclusions: A key feature of the next 5 years of the screening programme will be to maintain screening and rescreening.